Slab effects on response of reinforced concrete substructures after loss of corner column - Kai, Qian (2013)
In typical cast-in-situ construction, beams, columns and slabs act as a single structural unit. Ignoring the slab contribution to the strength and ductility of beams will result in a significant underestimation of the vertical force resistance. The influence of the slab on the strength of the floor system under imposed vertical deformation is significantly greater than would be anticipated by the interpretation of the current provisions for effective slab widths acting as a flange in a T-beam analysis. Therefore, in order to quantify the contribution of the slab towards progressive collapse of building structures in the blast environment, two series (F and S) of specimens were tested under monotonic loading to simulate axial loading in the corner column. The experimental results highlighting the behavior such as force-displacement responses, crack patterns, and failure mechanisms were discussed. Comparison of the performance of these two series of specimens indicated that incorporating the RC slab into the beam-column substructures would increase the ultimate resistant capacity by up to 63.0 % and significantly reduce the potential of progressive collapse.